Proportional Drawing Aid (PDA) / Muhammad Najibul Muthiie Che Yaacob - Che Yaacob, Muhammad Najibul Muthiie (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Proportional Drawing Aid (PDA) is a product that is specially designed to help artist during the process of producing drawing. This product gives a new dimension to the artist in order for them to get precise composition of the subject. The combination of window frame and eye wear is not only to facilitate the process of drawing to be more targeted and focused but also to reduce the physiological effect that can occur when traditional method of measurement is applied. In additional the application of grid on the PDA will help artist to get accurate proportion of the subjects without the need to move from ones current position.